Kontribusi Likuiditas, Leverage, dan Capital Intensity terhadap Agresivitas Pajak pada Perusahaan IDX 30 - Debi Eka Putri; Darwin Lie; Ady Inrawan; Sisca Sisca (Jurnal Ilmu Manajemen, 2021)
This study aimed to determine the effect of liquidity, leverage, and capital intensity on tax aggressiveness. The population in this study are all companies listed in the IDX during the research period: 2017-2020 and not in the banking sector. The sampling technique used is purposive sampling. The sample obtained is as many as 13 companies, with the number of observations being 52. The findings are that there is no significant effect between liquidity, leverage, and capital intensity on tax aggressiveness. At a high level of liquidity, the company can pay off its short-term obligations, including in terms of taxation. The leverage of small or large companies does not affect management to do tax avoidance. Companies with high fixed assets bear an increased tax burden as well. Some companies have set assets whose economic benefits have expired but are not derecognized and for movable assets.